2021
DOI: 10.3389/fphar.2021.747856
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and Vitamin D/Vitamin D Receptor Pathway Interaction: Potential Therapeutic Implications in Inflammatory Bowel Disease

Abstract: Inflammatory bowel diseases (IBD) are chronic conditions of unknown etiology and immunomediated pathogenesis. In the last years, the comprehension of the complex mechanisms involved in the intestinal mucosal homeostasis, and the analysis of the alterations potentially leading to inflammatory pathologic states, has consistently increased. Specifically, the extraordinary impulse in the field of research of the intestinal microbiome has opened the door to the investigation of possible novel approaches to the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
0
8
0
1
Order By: Relevance
“…As research progresses, it is increasingly evident that probiotic components could enhance intestinal epithelial barrier function [ 67 ]. Probiotics regulate intestinal epithelial homeostasis by promoting intestinal epithelial cell survival, enhancing barrier function, and stimulating protective responses while at the same time regulating host cell signaling pathways, including protein kinase B (Akt) signaling pathway, mitogen-activated protein kinase, and nuclear factor-κB [ 68 ]. Similarly, Rajput et al found that probiotics stimulate epithelial cells and activate dendritic cells through toll-like receptors, producing cytokines [ 69 ].…”
Section: Probiotics Regulate Immunity Through Intestinal Floramentioning
confidence: 99%
“…As research progresses, it is increasingly evident that probiotic components could enhance intestinal epithelial barrier function [ 67 ]. Probiotics regulate intestinal epithelial homeostasis by promoting intestinal epithelial cell survival, enhancing barrier function, and stimulating protective responses while at the same time regulating host cell signaling pathways, including protein kinase B (Akt) signaling pathway, mitogen-activated protein kinase, and nuclear factor-κB [ 68 ]. Similarly, Rajput et al found that probiotics stimulate epithelial cells and activate dendritic cells through toll-like receptors, producing cytokines [ 69 ].…”
Section: Probiotics Regulate Immunity Through Intestinal Floramentioning
confidence: 99%
“…Further experimental data demonstrated that probiotics stimulate VDR expression and activity. Besides the effect on VDR, some clinical and experimental data indicate that probiotic bacteria may increase vitamin D levels [ 34 ]. In the gut lumen, the mucus layer and the underlying epithelium serve to keep resident microbiota at bay [ 35 , 36 ].…”
Section: Vitamin D and Gut Microbiomementioning
confidence: 99%
“…A meta-analysis evaluating 16 studies including 1338 patients with IBDs and 808 controls has been published [78]. The mean ages (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) and gender distribution (49-53% women) were similar between the two groups. Along with a significantly lower mean BMD and Z-scores for IBD patients versus controls at all sites (femoral neck, total femur and lumbar spine), there was a significant 38% increase in global risk of fractures.…”
Section: Skeletal Impact Of Vitamin D Status In Ibdsmentioning
confidence: 99%
“…The interplay of bacterial metabolites, butyrate, and lithocholic acid, as well as bacterial enzymes (e.g., capable of activating vitamin D) and growth factors on VDR signaling and the course of inflammation, has also been explored [ 75 ]. Guidelines on the practical use of probiotics as valuable components of treatment in IBD are also expected in the future [ 79 ].…”
Section: Vitamin D Deficiency and Epigenetic Dysregulations In Autoim...mentioning
confidence: 99%